Characteristics and Outcomes of Neonates With Blood Stream Infection Due to Listeria monocytogenes. Issue 10 (October 2021) - Ntuli, Nandi; Wadula, Jeannette; Nakwa, Firdose; Thomas, Reenu; Van Kwawegen, Alison; Sepeng, Letlhogonolo; Seake, Karabo; Kgwadi, Dikeledi; Sono, Lino; Ondongo-Ezhet, Claude; Velaphi, Sithembiso
Abstract : Background: Infection due to Listeria monocytogenes (LM) is rare in neonates; thus, its clinical presentation and outcomes are not commonly reported, especially in low- and middle-income countries. In 2017, South Africa had an outbreak due to LM. Objective: To determine demographic characteristics, clinical and laboratory findings and outcomes of all neonates infected with LM during the outbreak period. Methods: This is a retrospective analytic study. Clinical and laboratory records of neonates admitted at Chris Hani Baragwanath Academic Hospital from January 2017 to May 2018 with positive blood and cerebrospinal fluid culture with LM were reviewed for demographic characteristics, clinical presentation, ancillary laboratory test results and outcomes at hospital discharge. Results: There were 42 neonates with positive cultures due to LM. Thirty-four (81%) were born preterm. Mode of delivery was vaginal in 78.6% and 31.0% were HIV exposed. All patients presented within the first 6 days of life as an early-onset disease. Common clinical presentation was respiratory depression (52.4%) and respiratory distress (38.1%) with 69% requiring invasive or noninvasive respiratory support. Common abnormal laboratory findings were high C-reactive protein (77.1%) followed by leukopenia (23.8%). Fourteen patients (40%) had features of meningitis based on blood and cerebrospinal fluid findings (4 culture proven). There were 11 deaths at hospital discharge, giving a mortality rate of 26.2%. Conclusions: The majority of neonates infected with LM were born preterm, raising the possibility that LM itself may have been responsible for preterm labor. All presented in the first 6 days of life and most presented with respiratory distress or depression. A high proportion had meningitis, and there was a high-mortality overall.